30-second brain : the 50 most mind-blowing ideas in neuroscience, each explained in half a minute - Seth, Anil.; Bekinschtein, Tristan (New York : Metro Books, 2001)
The 50 most mindblowing ideas in neuroscience, each explained in half a minute.
Building the brain -- Brain theories -- Mapping the brain -- Consciousness -- Perception & action -- Cognition & emotion -- Changing brain.
Includes bibliographic references and index.
Keywords: Cognitive neuroscience -- Popular works; Brain -- Popular works